A Streamlined DNA Tool for Global Identification of Heavily Exploited Coastal Shark Species (Genus Rhizoprionodon) - Pinhal, Danillo; Shivji, Mahmood S.; Nachtigall, Pedro G.; Chapman, Demian D.; Martins, Cesar (PloS one, 2012)
Obtaining accurate species-specific landings data is an essential step toward achieving sustainable shark fisheries. Globally distributed sharpnose sharks (genus Rhizoprionodon) exhibit life-history characteristics (rapid growth, early maturity, annual reproduction) that suggests that they could be fished in a sustainable manner assuming an investment in monitoring, assessment and careful management. However, obtaining species-specific landings data for sharpnose sharks is problematic because they are morphologically very similar to one another. Moreover, sharpnose sharks may also be confused with other small sharks (either small species or juveniles of large species) once they are processed (i.e., the head and fins are removed). Here we present a highly streamlined molecular genetics approach based on seven species-specific PCR primers in a multiplex format that can simultaneously discriminate body parts from the seven described sharpnose shark species commonly occurring in coastal fisheries worldwide. The species-specific primers are based on nucleotide sequence differences among species in the nuclear ribosomal internal transcribed spacer 2 locus (ITS2). This approach also distinguishes sharpnose sharks from a wide range of other sharks (52 species) and can therefore assist in the regulation of coastal shark fisheries around the world.